254 views
0 votes
Help? #7 I did it but the answer was wrong...I have the answers I need explanation

Help? #7 I did it but the answer was wrong...I have the answers I need explanation-example-1
User EarlyRiser
by
6.6k points

1 Answer

4 votes

7.


(3^4x^4)/(3x^2) = 3^(4 - 1)x^(4 - 2) = 3^3x^2 = 27x^2

10.


((-2)^5 * (-3)^4 * (-5)^3)/((-2)^3 * (-3) * (-5)^2) =


= ((-2)^5 * (-3)^4 * (-5)^3)/((-2)^3 * (-3)^1 * (-5)^2)


= (-2)^(5-3) * (-3)^(4-1) * (-5)^(3-2)


= (-2)^(2) * (-3)^(3) * (-5)^(1)


= (-2) * (-2) * (-3) * -3 * (-3) * (-5)


= 4 * (-27) * (-5)


= 540

User Marcosdsanchez
by
6.5k points